A palynological perspective on the tribe Viteae of the grape family (Vitaceae). Issue 1 (2nd January 2022) - Cartaxo-Pinto, Simone; Paulo, Gabriel Henrique Cardoso; Jackes, Betsy R.; Gonçalves-Esteves, Vania; Mendonça, Claudia Barbieri F.
Abstract: The tribe Viteae comprises about 200 species and is represented by the genera Vitis and Ampelocissus. Vitis is the most studied genus within the grape family (Vitaceae) because of the global economic importance of its fruits and derived products. This study examined the palynology of Ampelocissus and Vitis species belonging to the tribe Viteae to identify pollen characters that may contribute to the taxonomic and morphological characterisation of Ampelocissus . Pollen specimens were obtained from herbaria, treated by the acetolysis method, measured, photographed, and described using light and scanning electron microscopy. In the analysed species, pollen grains were isopolar or heteropolar, medium-sized, tricolporate, oblate spheroidal to subprolate. Ornamentation patterns differed among species, with examples of bireticulate, microreticulate, perforate, reticulate, and rugulate sexine. These characters were used for the development of a pollen key to the genera. Principal component analysis revealed that quantitative pollen characters were the most important for group discrimination. This study contributes to the palynological knowledge of some undescribed species and provides novel palynotaxonomic information on the family Vitaceae.